Entrepreneurial Orientation Literature Review: Measurement - Eka Zahra Solikahan; Ali Mohammad (Journal of International Conference Proceedings (JICP), 2018)
Entrepreneurial orientation EO is a practice that provides basic results and entrepreneurial action. Therefore, this study aims to explain the development of entrepreneurship orientation (EO) and its measurement based on previous research using a qualitative approach with literature research methods (library research). Finding that EO is an entrepreneurial model focused on management strategies and also used to measure EO is Proactive, Innovative, risk-taking, Competitiveness, Autonomy, Competitive Energy. Keywords: Entrepreneurial Orientation, Entrepreneurship, Entrepreneurial Orientation Measurement